PENGARUH MODAL MANUSIA TERHADAP PENDAPATAN DAERAH KABUPATEN BOJONEGORO TAHUN 2010-2021 - Romadhoni, Bagus Abdi; Fadil, Faishal (Journal of Development Economic and Social Studies, 2023)
Increasing economic growth is the main goal of regional development, including the Bojonegoro Regency. However, according to the BPS of East Java Province, Bojonegoro Regency experienced a decline in economic growth in 2020 and 2021, namely around -0.04% and -5.04%. Even in 2021, Bojonegoro Regency will be the region with the lowest economic growth in East Java. Economic growth is influenced by many factors, some of which are educational factors, health factors, and labor factors. Therefore, this study was formed to know the effect of Net Enrollment Rate, Life Expectancy Rate, and Total Labor Force on the Gross Regional Domestic Product in Bojonegoro Regency in 2010-2021 with Inflation controlled. This study uses a quantitative method with Multiple Linear Regression Analysis. The sampling technique used in this study is the saturated sample technique or total sampling. The results of the analysis show that life expectancy and inflation have a significant negative effect, while net enrollment rates and total workforce have a significant positive effect on GRDP in Bojonegoro Regency in 2010-2021.